Scollay Square, May 30, 1961 - Unknown (Tufts Archival Research Center, 2005)
Street-level view northeast of Scollay Square. Signage adorns buildings lining both the south-southeast and north-northwest sides of Cornhill, which is visible in the background of the photograph. Automobiles, street lights, traffic signs and traffic lights are visible on Court Street and Cornhill, and pedestrians are included in the photograph. A subway entrance is visible along the lower-left side of the photograph. 3 x 3, 3 1/2 x 3 1/2 overall Photographs